Administrative Offense and Crime: What Is the Difference? - Shevchenko, Yurii P.; Kositsin, Igor A. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article deals with the problem of classification of unlawful, guilty, punishable, dangerous or harmful for society activities. Between the criminal and administrative responsibility of the similarity is greater than the difference. The existing differences cease to play a decisive role in isolating these types of responsibility. Argumenting their position, the authors turn to the foreign experience, the decisions of the European Court of Human Rights.